The Effect of Professional Allowances on Work Motivation and Performance of Elementary School Teachers in Cluster II, Sorong City, Southwest Papua - Hasan Yusuf Masani; Misriandi Misriandi; Muhamad Sofian Hadi; Gamal Marinyo (Jurnal Ilmiah Profesi Pendidikan, 2026)
Teacher professional allowance is a strategic government policy intended to improve teachers' welfare, work motivation, and performance. However, better welfare does not always directly lead to better professional practice. This study analyzes the relationship between professional allowance, work motivation, and teacher performance among elementary school teachers in Cluster II, Sorong City, Southwest Papua. The study used a quantitative correlational design. Data were collected through questionnaires, observation, interviews, and literature study. The population comprised elementary school teachers in Cluster II, while the sample focused on certified teachers who received professional allowances. The research instruments measured professional allowance, work motivation, and teacher performance and were tested for validity and reliability. The findings show that professional allowance has a positive and significant relationship with teacher motivation, with a correlation coefficient of 0.515 and a determination coefficient of 26.52%. The relationship between professional allowance and teacher performance is very strong, with a correlation coefficient of 0.894 and a determination coefficient of 79.92%. These findings indicate that professional allowance strengthens teacher professionalism, although motivation still requires support from leadership, work climate, organizational culture, and continuous professional development.